Influence of Work Environment on the Psychological Well-being and Quality of Life of Some Selected Uniform Officers in Benin City - Aideyan, Daniel Osarenmwanta; Olikiabo, Samuel Osarentin (Journal of Health Promotion, 2025)
The study investigates the influence of work environment on the psychological well-being and quality of life of some selected uniform officers in Benin City. Four hypotheses were formulated as the descriptive survey research design was used. From a population of 624 of selected uniform officers which comprised of the police and the Federal Road Safety Corp (FRSC) officers, 236 officers were selected as the sample using the stratified and purposive sampling techniques. An adapted Ryff ’s Psychological Well-being Scale and Mahmood’s Quality of Life measurement scale were used. Psychometric properties of the instrument were ascertained. Collected data were analyzed using t-test. The findings revealed that there exists a significant difference in the psychological wellbeing and quality of life of police officers and FRSC officers who work in the office and those on the highways. Police officers working in the office had significantly higher psychological wellbeing scores than those on the highway (t=1.169, df=234, P=0.020) and also demonstrated better quality of life (t=1.158, df=234,P=0.022). Similarly, FRSC officers in office settings recorded significantly higher psychological wellbeing (t=1.171, df=234, P= 0.024) and quality of life (t=1.166, df=234, P=0.027) compared to their highway counterparts. In conclusion, work environment is a principal concept in determining the level of psychological well-being, quality of life of the studied uniform officers. Therefore, management of security officers should periodically carry out work environment assessment in relation to job satisfaction, psychological wellbeing with work benefits such as leave, vacation, and retreat granted to uniform officers at least twice a year.